Urinary tract infections in Portugal: A decade of evidence on uropathogens and antimicrobial resistance — A systematic review - Rodrigues, Francisco (2026)
Background: Urinary tract infections (UTIs) are among the most common bacterial infections worldwide and represent a significant public health concern due to their high prevalence and increasing antimicrobial resistance. This study aimed to systematically review the epidemiology, uropathogens, and resistance patterns of UTIs in Portugal over the last decade. Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. A literature search was performed in April 2026. A total of 425 records were identified. After removal of duplicates and preliminary exclusions, 121 records were screened by title and abstract. Following application of eligibility criteria, 41 full-text articles were assessed, of which 13 met the criteria for detailed eligibility assessment. Six studies met the inclusion criteria and were included in the final qualitative synthesis. Results: The included studies consistently reported a higher prevalence of UTIs in females and, in some cases, in older populations. Escherichia coli was identified as the predominant uropathogen across all studies, followed by Klebsiella pneumoniae, Proteus spp., and Enterococcus spp. A consistently high prevalence of antimicrobial resistance was observed, particularly against commonly used antibiotics such as ampicillin and trimethoprim–sulfamethoxazole. The presence of extended-spectrum β-lactamase (ESBL)-producing strains was also reported, especially in healthcare-associated infections, which exhibited higher resistance profiles compared to community-acquired infections. Conclusions: The available evidence suggests that UTIs in Portugal are predominantly caused by enterobacteria, particularly Escherichia coli. However, the limited number and heterogeneity of studies highlight the need for cautious interpretation. Further multicenter and methodologically robust studies are required to better characterize national epidemiological patterns and antimicrobial resistance trends.